Sticking together and sorting things out: adhesion as a force in development. - McNeill, H. (Nature Reviews. Genetics, 2000)
During development it is not sufficient for cells to differentiate properly--they must also become physically grouped into appropriate structures, to form skin on the outside, and blood and muscle on the inside. How does this three-dimensional patterning occur? One classic explanation for this resolution of cells and tissues into distinct three-dimensional structures has been that as cells differentiate, they develop differential adhesive properties, and that these affinity differences allow cells to sort out from one another. This classic hypothesis is being investigated with increasing intensity, as recent work on the Drosophila wing and the vertebrate brain has shown that signalling between tissues is essential for the establishment of differential affinities.